1999
DOI: 10.2307/4003497
|View full text |Cite
|
Sign up to set email alerts
|

Central Nevada Riparian Areas: Physical and Chemical Properties of Meadow Soils

Abstract: Despite the importance of soil characteristics for classifying riparian ecosystem types and evaluating ecosystem or range condition, little information exists on western riparian area soils or the factors that influence them. We examined the effects of drainage basin geology and water table depth on soil morphology and soil physical and chemical properties of meadow sites in central Nevada. We described and analyzed the soils of meadows that occurred in 4 drainages with different geology and that exhibited hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Flooding recedes as the summer progresses, resulting in pools ranging in size from > 100 m 2 in the spring to more discrete pools (~1 m 2 ) later in the season [26]. All study meadows were identified as wet (0-30 cm depth to water table) or mesic (30-80 cm water table depth) based on both literature review [29,30] and field visits [31]. Meadow soils were classified as Mollisols and Inceptisols with Histosols found in the wettest meadow areas [26].…”
Section: Methodsmentioning
confidence: 99%
“…Flooding recedes as the summer progresses, resulting in pools ranging in size from > 100 m 2 in the spring to more discrete pools (~1 m 2 ) later in the season [26]. All study meadows were identified as wet (0-30 cm depth to water table) or mesic (30-80 cm water table depth) based on both literature review [29,30] and field visits [31]. Meadow soils were classified as Mollisols and Inceptisols with Histosols found in the wettest meadow areas [26].…”
Section: Methodsmentioning
confidence: 99%
“…al. 2001), that is being exacerbated by anthropogenic disturbance (Chambers et al 1999) and riparian ecosystem characteristics (Castelli et al 2000). Thus, the potential for restoring sagebrush-dominated ecosystems to grass and sedge meadows depends on whether or not an abiotic threshold defined by water table depth has been crossed (Chambers and Linnerooth 2001 (Weixelman et al 1996).…”
mentioning
confidence: 99%
“…Within riparian areas, the physical and chemical properties of soils are inherently variable at both small and large spatial scales (Chambers et al, 1999). Because of this variability, more comprehensive methods are needed to correctly classify and evaluate riparian areas.…”
Section: Discussionmentioning
confidence: 99%